PEMANFAATAN EKSTRAK WORTEL (Daucus carota L.) DAN SARI KIWI KUNING (Actinidia deliciosa) DALAM PEMBUATAN PERMEN JELI [Utilization of Carrot (Daucus carota L.) Extract and Gold Kiwi (Actinidia deliciosa) Juice in the Making of Jelly Candy] - Melanie Cornelia; Christy Nathania (FaST - Jurnal Sains dan Teknologi (Journal of Science and Technology), 2020)
Carrot is a vegetable with high  β -carotene content as pigment  as natural colorant, which both have many health benefits. Gold kiwifruit is a fruit with high vitamin C content. Therefore those micro nutrients and the pigment can be used in the development of food products. Jelly candy is liked by many but generally has low nutrition. This research aims to utilize carrot extract and gold kiwifruit juice in the making of attractive and nutritious candy jelly which is liked by many people. The method used is extraction of carrots and making juice from yellow kiwi and it is formulated to make jelly candy.The juice was obtained from gold kiwi fruits that were crushed with juicer and filtered. Carrots were extracted by maceration with three solvents (hexane, ethyl acetate, ethanol) and extraction time (24, 48, 72 hours) to obtain the best extract. The result is hexane and extraction time of 48 hours gave the best extract with IC50 value of 2036.25 ± 67,73 mg/l and β-carotene content of 11.422 ± 0,568 mg/100 g. The yellow kiwi juice and selected carrot extract were made formulations with addition carrot extract variables 0.2%, 0.4%, 0.6%, 0.8% and 1% mixed with yellow kiwi juice and heated to 78-800C and molded as jelly candy. The conclusion is the selected jelly candy is made with the addition of carrot extract  0.8%, has an IC50  of 23042.13 ± 832.87 mg / l, β -carotene  8.678 ± 0.068 mg / 100 g, yellowish red color, and is a candy the panelists liked the most. Apart from having an attractive color appearance, this jelly candy have healthy benefit which is contains high beta carotene as an antioxidants.AbstrakWortel adalah sayuran yang banyak mengandung beta-karoten yaitu pigmen warna yang dapat dimanfaatkan sebagai pewarna alami dan memiliki banyak manfaat kesehatan. Kiwi kuning adalah buah dengan kandungan vitamin C yang tinggi. Kandungan mikro nutrisi dan pigmen warna tersebut dapat dimanfaatkan dalam pembuatan produk pangan. Permen jeli disukai banyak orang namun umumnya memiliki nutrisi yang kurang baik. Penelitian ini bertujuan untuk memanfaatkan ekstrak wortel dan sari kiwi kuning dalam pembuatan permen jeli yang bernutrisi, penampilan menarik dan disukai banyak orang. Sari kiwi kuning diperoleh dari kiwi kuning yang dihancurkan dengan juicer dan disaring. Wortel diekstrak dengan metode maserasi menggunakan tiga pelarut (heksana, etil asetat, etanol) dan waktu ekstraksi (24, 48, 72 jam) untuk mendapatkan ekstrak terbaik. Pelarut heksana dan waktu maserasi 48 jam memberikan hasil ekstrak terbaik dengan nilai IC50 2.036,25 ± 67,73 mg/l dan kadar beta-karoten 11,422 ± 0,568 mg/100 g. Sari kiwi kuning dan ekstrak wortel terbaik diformulasi menjadi permen jeli. Permen jeli terpilih adalah permen jeli yang terbuat dari sari kiwi kuning dengan penambahan ekstrak wortel sebanyak 0,8% dengan nilai IC50 sebesar 23.042,13 ± 832,87 mg/l, kadar beta-karoten sebesar 8,678 ± 0,068 mg/100 g, warna merah kekuningan, dan merupakan permen yang paling disukai panelis.